ANTICOAGULANTS AND EPISTAXIS: A COMPARATIVE ANALYSIS OF EPISTAXIS WITH WARFARIN AND DIRECT ORAL ANTICOAGULANTS - AZHAR , S; AHMED , SI; MUKHTAR , A; AZHAR , H; HASSAN , A; HASHIR, Z (Biological and Clinical Sciences Research Journal, 2023)
Anticoagulant therapy prevents and treats thromboembolic occasions like profound vein thrombosis, pneumonic embolism, and stroke. Warfarin, a vitamin K bad guy, has been the standard oral anticoagulant for quite some time. The study's main objective is to find that warfarin is associated with higher rates of epistaxis compared to direct oral anticoagulants. This cross-sectional study was conducted at Islamabad Medical and Dental College, Islamabad, from January 2023 till July 2023. Data was collected from 123 patients of both genders. The study population consists of adult patients prescribed anticoagulant therapy for various indications, including atrial fibrillation, venous thromboembolism, and mechanical heart valve replacement. Patients were identified from electronic medical records at the study site. In this study, a total of 123 adult patients receiving anticoagulant therapy were included. Among them, 62 patients were prescribed warfarin, and 61 were on direct oral anticoagulants (DOACs) (rivaroxaban, dabigatran, apixaban, or edoxaban). Warfarin and DOACs demonstrated similar safety profiles regarding other bleeding events and major adverse events. It is concluded that the study found no statistically significant difference in the incidence of epistaxis between the two treatment groups. Both Warfarin and DOACs showed similar safety profiles regarding other bleeding events and major adverse events, indicating that they are generally well-tolerated options for anticoagulation therapy in this patient population.